Perspectives on the 12 January 2020 Taal Volcano eruption: An analysis of residents’ narrative accounts - Martinez-Villegas, Ma. Mylene; Reniva, Paolo D.; Sanico, Lucille Rose D.; Loza, Allan R.; Seda, Ricardo G.; Doloiras, Dynie F.; Pidlaoan, Abigail C. (Frontiers in Earth Science, 2022)
This study reconstructs the 12 January 2020 Taal Volcano eruption through the analysis of narratives from two perspectives: those of the Taal Volcano Island (TVI) residents and those living along the Taal Caldera Lakeshore (TCLS). Personal accounts of TVI residents provide an up-close look at the volcano’s behavior from the day before the eruption to the escalation of volcanic activity until the early morning after the eruption. These also include information on individual actions that helped lead to community evacuation. The decisions and resulting actions of TVI residents highlight the importance of alertness to observations of changing volcano behavior (environmental cues) based on local knowledge and long-established communication between the monitoring agency and the residents who had trust in the received warning message during the unfolding event. These paved the way for the quick action of the residents to evacuate at the most critical time. Interviews of eyewitnesses from TCLS on the other hand suggest a spectator’s first reaction to watching the motorized outrigger boats as TVI residents evacuated (social cues), waiting before taking action to evacuate themselves. While various information and education efforts were conducted in the years leading to the 2020 event, the lack of experiential knowledge among the lakeshore residents and the fact that Taal did not have any major eruption in more than 40 years mainly contributed to their hesitancy to immediately evacuate, and not until the eruption occurred.